MYTHOLOGICAL OVERTONES IN GEETANJALI SHREE’S TOMB OF SAND - Ankita (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Geetanjali Shree’s Tomb of Sand intricately weaves mythological elements into the fabric of its narrative, creating a rich tapestry that reflects the complexities of identity, gender, and the socio-political landscape of contemporary India. This paper explores how Shree employs mythological motifs, characters, and themes to enrich her storytelling, examining the interplay between personal and collective histories. Through a detailed analysis, this research aims to uncover the layers of meaning embedded within the text, revealing how mythological overtones serve to enhance the reader's understanding of the protagonist's journey and the broader cultural context.